Results of the Methodology of Teaching Foreign Languages to Medical Universities (Texas Journal of Philology, Culture and History, 2023)
This article discusses the methodology of foreign language teaching, the history of its development as a science, the types of modern methods used in foreign language teaching methods and their use.